The nature of the social customs and traditions of Bani Tamim in Diyala and their relationship to their social environment (1914-1958 AD) (Journal of the College of Basic Education, 2023)
The research follows the nature of the social customs and traditions of Bani Tamim in Diyala and their relationship to their social environment during the period (1914-1958 AD). The research material was distributed on four axes, an introduction and a conclusion. The first axis dealt with: (the social and religious composition in Diyala and the impact of the Bani Tamim therein 1914-1958 AD), and the second axis dealt with (the customs of the Bani Tamim clans, their costumes and their social traditions), and the third axis shed light on (the impact of Banu Tamim in the spatial and demographic structure and factors of migration from the countryside to the city in Diyala 1921-1958 AD), and follows the fourth axis (Banu Tamim social relations during the royal era). The research relied on a lot of various sources and references, which contributed to its completion and output in the way it is, the most important of which is the master's thesis tagged: (Economic and Social Life in Diyala 1908-1921 AD) by the researcher Ali Fadel Al-Ugaili, and the research of Dr. Qahtan Hamid Kazem, which is tagged: (Diyala in the years of the World War The first), and conducting personal interviews with a number of current Bani Tamim sheikhs and a number of academics and female relatives with experience in the history of Iraqi clans. In addition to many sources and references, its details are recorded in the margins and sources at the end of the research. The research reached the following conclusions:1.The obvious social impact of Bani Tamim was represented in building strong and balanced social relations in Diyala, as its sheikhs of prestige, wisdom, and a great deal of courage and generosity worked hard to resolve many of the tribal and clan disputes that existed in Iraqi tribal society at that time, adopting peaceful and friendly methods. Most of the time, after resorting to the logic of reason and wisdom and relying on the authentic Arab tribal customs and traditions and the rulings of the true Islamic religion, but at the same time they defended the interests of the people of their tribe and those who protected them by force of arms if necessary.2.The Bani Tamim tribe in the Diyala district played an important role in drawing a beautiful picture of peaceful coexistence between the national, religious and tribal components of Diyala. They lived in simple houses that did not protect many of them from the summer heat and the winter cold. They wore various and simple clothes according to their places of residence and their level of living. The sons of other clans in their joys and sorrows.3.The people of Tamim in Diyala adhered to the traditions of marriage and betrothal that they inherited from their ancestors, and faced many other problems, starting with negative feudal practices, poor living conditions, and the spread of diseases due to the lack of healthy food and the abundance of swamps and continuous floods, and the government’s pursuit of them to include them in conscription, which prompted many Some of them migrated internally to the cities of Diyala and the outskirts of Baghdad, and the population censuses showed a clear growth in their population, which increased their social weight in Diyala at the end of the research period.